Effects of spacing on early growth rate and carbon sequestration in Pinus brutia Ten. plantations - Nesat Erkan; Ali C. Aydin (Forest Systems, 2016)
Aim of study: The aim of this study was to analyze the effects of initial spacing on early growth and carbon sequestration rates in Turkish red pine plantations up to 12 years old, established with improved seeds and deep soil cultivation. Area of study: The study was conducted on experimental sites established in two locations within the Turkish red pine natural distribution areas, namely Duacı and Nebiler close to Antalya city. Material and methods: Data were collected from the experimental sites established as a Nelder design (fan-shaped), with 72 rays and 18 arcs (circles), and trees were planted (almost square) at distances ranging from 1.15 to 4.77 m. Soil type of both sites is loamy, with soil clay content varying between 70-87% in Duacı and 51-70% in Nebiler. Soils are deep being more than one m in both sites, but rockier in Nebiler, providing better soil drainage in this site. Main results: The results showed that mean total height was greater at closer spacing than those of wider spacing until age eight. Growth retardation at wider spacing in early years may be related to water loss due to evaporation in hot summer days and weed suppression. Following the age eight, competition among trees appears to be the major factor reducing the growth and carbon fixation. Diameter at breast height and individual tree volume increased, while stand volume, mean annual volume increment and annual carbon storage per hectare considerably decreased for wider spacing. Our results suggest that in order to obtain higher yield and more carbon fixation, short rotation plantations should initially be established in closer spacing, followed by thinning in subsequent years as required by silvicultural concerns. In this context, spacing 3.0 × 1.0 m or 3.0 × 1.5 m (3.0 and 4.5 m2 growing area per tree, respectively) seems to be more plausible, providing farm machinery for maintenance and harvesting. We also found that mean annual volume increment per unit area can be considerably increased by using improved seed and deep soil cultivation in plantations. Research highlights: Results encourage managers for short rotation management in industrial plantations using closer spacing in terms of carbon sequestration as well as wood production.